Reliability and validity of Polar Team Pro measurements in running at different velocities in an indoor setting - van den Tillaar, Roland; Gaustad Pettersen, Fredrik; Lagestad, Pål (Frontiers in Sports and Active Living, 2023)
The purpose of this study was to test the reliability and validity of Polar Team Pro measurements of velocity, acceleration, and distance covered in a rectangular run at different intensities in an indoor setting. In two test sessions, 10 women (age 15.7 ± 0.4 years, body mass 61.3 ± 5.3 kg, body height 1.69 ± 0.07 m) performed 100 m runs at different intensities, ranging from 8 to 18 km/h. The 100 m runs were performed on a rectangular track at an indoor handball facility. The main finding revealed that Polar Team Pro underestimated the running distance and velocity (10%–15% at 10 km/h), especially at higher speeds (15% and 6% at 15 and 18 km/h, respectively). Between test days, coefficients of variance varied from 4.2% to 12.4%, when measuring at different speeds. However, a significant difference was found for the two runs only at 15 km/h between the two test days. It was concluded that Polar Team Pro underestimated the running distance and velocity when measuring a rectangular run at different speeds in an indoor setting, especially at higher speeds. This underestimation is probably caused by the inaccuracy of the inertial measurement unit algorithm that calculates the distance, as body height influences the distance and velocity measurements. The variability between the different units is, thereby, also influenced, causing variable coefficients of variance between the sensors. Test–retest variability was acceptable. Based on the findings of this study, practitioners should be cautious when measuring speed and distance using Polar Team Pro Sensors in indoor settings, as these measurements are underestimated with increasing speed.